Pleomorphic adenoma treatment in a patient with neurodegenerative disease: case report - Iandra Luah Souza Maia; Paula Patrícia Santos Santos; Antonio Carlos Marqueti; Paulo Henrique Luiz de Freitas; Rosany Larissa Brito de Oliveira; Álvaro Bezerra Cardoso (RGO: Revista Gaúcha de Odontologia, 2024)
ABSTRACT Pleomorphic adenoma (PA) is a benign tumor, responsible for more than 50% of the cases of salivary gland neoplasms, occurring both the major and minor salivary glands. In the oral cavity, the most frequent sites of pleomorphic adenoma are the palate and the lips, with greater preference for females and frequently affecting individuals in the fourth to fifth decade of life. The treatment of choice is based on total lesion excision with a good prognosis, which has a low potential for recurrence and malignant transformation. The objective of the study was reporting a treatment of pleomorphic adenoma localized in the hard palate of the 74-year-old male patient, F.A.S. with Parkinson’s disease. The patient is in outpatient follow-up for over a year with no signs of recurrence. Computed Tomography is an indispensable tool for directing the correct diagnosis, which is only definitive after the histopathological examination. The most indicated treatment with good prognosis is complete surgical excision of the lesion and curettage.